A Systematic Review of Grey Literature on Outreach Activity Management Tools - Fell, Lucas; Dalepiane, Igor; Fialho, Matheus; Bernardino, Maicon (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na Educação, 2024)
This paper presents a systematic review of grey literature focused on existing tools and solutions for managing outreach activities in the context of Higher Education Institutions (HEIs). Given the mandatory integration of outreach activities into the curriculum starting in 2023, this review aims to identify relevant tools, assess their features, and inform the development of a new management tool currently in progress. The study follows a structured methodology, applying rigorous inclusion and exclusion criteria to filter and evaluate relevant tools. Initial findings highlight key functionalities and common challenges in the current landscape, providing a foundation for the ongoing development of our solution.